Ion channels and disease : channelopathies - Ashcroft, Frances M. (Academic Press, 2000)
Ion channels are membrane proteins that act as gated pathways for the movement of ions across cell membranes. They play essential roles in the physiology of all cells. In recent years, an ever-increasing number of human and animal diseases have been found to result from defects in ion channel function. Most of these diseases arise from mutations in the genes encoding ion channel proteins, and they are now referred to as the channelopathies. Ion Channels and Disease provides an informative and up-to-date account of our present understanding of ion channels and the molecular basis of ion channel diseases. It includes a basic introduction to the relevant aspects of molecular biology and biophysics and a brief description of the principal methods used to study channelopathies. For each channel, the relationship between its molecular structure and its functional properties is discussed and ways in which genetic mutations produce the disease phenotype are considered. This book is intended for research workers and clinicians, as well as graduates and advanced undergraduates. The text is clear and lively and assumes little knowledge, yet it takes the reader to frontiers of what is currently known about this most exciting and medically important area of physiology. Key Features * Introduces the relevant aspects of molecular biology and biophysics * Describes the principal methods used to study channelopathies * Considers single classes of ion channels with summaries of the physiological role, subunit composition, molecular structure and chromosomal location, plus the relationship between channel structure and function * Looks at those diseases associated with defective channel structures and regulation, including mutations affecting channel function and to what extent this change in channel function can account for the clinical phenotype.